2019
DOI: 10.3389/fphar.2019.01010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety in the Continued Treatment With a Biosimilar Drug in Patients Receiving Infliximab: A Systematic Review in the Context of Decision-Making From a Latin-American Country

Abstract: Introduction: Biological products, including infliximab (INF), are a therapeutic option for various medical conditions. In the Peruvian Social Security (EsSalud), infliximab is approved for the treatment of rheumatoid arthritis, psoriasis, psoriatic arthropathy, ankylosing spondylitis, ulcerative colitis and Crohn’s disease (in cases refractory to conventional treatment). Biosimilars are a safe and effective alternative approved for these diseases in patients who start treatment with infliximab. Nevertheless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…Previous literature reviews have evaluated safety and efficacy of switching to biosimilar infliximab from the reference product. Unlike our study, these reviews were limited to a single disease (IBD) 51 or setting 52 . Nonetheless, some limitations of this review should be noted.…”
Section: Discussionmentioning
confidence: 91%
“…Previous literature reviews have evaluated safety and efficacy of switching to biosimilar infliximab from the reference product. Unlike our study, these reviews were limited to a single disease (IBD) 51 or setting 52 . Nonetheless, some limitations of this review should be noted.…”
Section: Discussionmentioning
confidence: 91%
“…Data on teratogenic effects of TNFi are limited and there is no strong evidence of potentially harmful effects, if used in preconception period [ 32 ]. Recent data and metanalysis suggest that biosimilar drugs are equal to their biooriginators, however, recent data have shown that treatment with biosimilar ADA, ETN and IFX might be associated with increased discontinuation rates due to medical and nonmedical issues, such as the nocebo effect [ 34 , 35 , 36 , 37 , 38 , 39 ]. Moreover, researchers from the UK suggest that nonmedical switch from biooriginal to biosimilar drug might involve higher costs from the medical system than continuation of the original drug [ 40 ].…”
Section: Bdmards Based On Cytokine-targeted Therapymentioning
confidence: 99%
“…63 The Peruvian Social Security (known as Es-Salud) reported biosimilarity between infliximab and CT-P13, and according to financial analysis determined it is a cost-effective decision. 64 In 2013, Park and colleagues 65 reported a Phase 1, doubleblind, parallel-group study of 22 and 30 weeks on 250 patients administered with either CT-P13 (n = 125) or infliximab (n = 125) (in two groups). To check the efficacy and safety profile, concentration-time curve (AUC) at steady-state and observed maximum steady-state serum concentration (C max , ss) was evaluated.…”
Section: Prospective Role Of Ct-p13 In Ibdmentioning
confidence: 99%